A Japanese TTS system based on multiform units and a speech modification algorithm with harmonics reconstruction. - Takano, S.
This paper proposes a new text-to-speech (TTS) system that utilizes large numbers of speech segments to produce very natural and intelligible synthetic speech. There are two innovations; new multiform synthesis units and a new speech modification algorithm based on a vocoder that offers harmonics reconstruction. The multiform units make it possible to reduce acoustic discontinuities at concatenation points and unnatural sound by preparing synthesis units with various lengths and various F0 contours. The new speech modification algorithm, on the other hand, improves the quality of prosody modified speech. This algorithm is extremely effective in synthesizing speech whose prosodic parameters are quite different from those of synthesis units. Listening tests confirm that the new synthesis units yield speech with high intelligibility and naturalness, and that the new speech modification algorithm is superior to all other conventional vocoders and waveform domain algorithms including TD-PSOLA, especially when modifying the F0 frequency upward
Keywords: Japanese TTS system; Acoustic discontinuities; Concatenation points; Harmonics reconstruction; Intelligibility; Multiform synthesis units; Multiform units; Naturalness; Prosody modified speech; Speech modification algorithm; Speech segments; Text-to-speech synthesis system; Unnatural sound; Vocoder